Live attenuated COVID-19 vaccines: approaches to development and prospects for clinical use - Ekaterina R. Korchevaya; Anastasiia V. Gracheva; Ilya N. Dyakov; Vitaly V. Zverev; Evgeny B. Faizuloev (Журнал микробиологии, эпидемиологии и иммунобиологии, 2023)
Although WHO declared an end to the pandemic, COVID-19 remains a significant public health concern worldwide. Modern vaccines often induce either only humoral or only cellular immunity. Furthermore, new emergent epidemiologically significant SARS-CoV-2 variants and their spread considerably reduce the effectiveness of preventive vaccination. Therefore, there is an urgent need to improve the existing vaccines against COVID-19. One of the promising approaches to the solution of the problem is creation of a "universal" vaccine that would have a cross-protective activity against different antigenic variants of the virus. In this respect, the development of live attenuated vaccine is of special interest, as it can activate not only humoral, but also cell-mediated components of immunity, providing long-term immune response and cross-protection against different variants of the virus.